ChemInform Abstract: A Palladium‐Catalyzed Addition Reaction of Aroyl/Heteroaroyl Acid Anhydrides to Norbornenes. Issue 15 (April 2015) - Arisawa, Mieko; Tanii, Saori; Yamaguchi, Masahiko
Abstract: The reaction gives exclusively the 2, 3‐trans adducts.